2005
DOI: 10.1111/j.1600-6143.2005.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sirolimus with Low‐Dose Tacrolimus Versus Sirolimus‐based Calcineurin Inhibitor‐Free Regimen in Live Donor Renal Transplantation

Abstract: , 132 live donor renal allotransplant recipients were included in a prospective, randomized controlled trial where they were divided into two groups. All patients received steroids and basiliximab induction therapy. For maintenance immunosuppression, tacrolimus and sirolimus were used in group A. In group B, mycophenolate mofetil (MMF) and sirolimus were utilized. Patients were followed up for a minimum of 24 months. One-year patient and graft survival rates were not significantly different between group A (96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 27 publications
4
74
0
2
Order By: Relevance
“…15 We have previously reported on the 2-yr safety and efficacy profile of SRL/steroids based regimens in combination with either low-dose Tac (group A) or MMF (group B) together with basiliximab induction therapy among live-donor renal allotransplant recipients in a prospective randomized study, and it was shown that the SRL/MMF regimen was safe regarding patient and graft survival and was associated with significant better renal function at 2 yr than the Tac/SRL regimen. 14 We hereby report on the long-term safety and efficacy profile of the same randomized patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…15 We have previously reported on the 2-yr safety and efficacy profile of SRL/steroids based regimens in combination with either low-dose Tac (group A) or MMF (group B) together with basiliximab induction therapy among live-donor renal allotransplant recipients in a prospective randomized study, and it was shown that the SRL/MMF regimen was safe regarding patient and graft survival and was associated with significant better renal function at 2 yr than the Tac/SRL regimen. 14 We hereby report on the long-term safety and efficacy profile of the same randomized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on intention-to-treat analysis, statistically significant higher renal function obtained at 2 yr among SRL/MMF patients, 14 was maintained until the last follow-up period, a finding that comes in accordance with all short-term 12,13,20 and long-term studies 16 ; however, more recently, Larson et al, 21 in a comparison of TAC/MMF versus SRL/MMF, showed that the iothalamate clearance at 1 mo was higher in the SRL/MMF than in the TAC/MMF group (67 Ϯ 18 ml/min versus 58 Ϯ 17 ml/min); however, this difference was lost at 1 yr because of the unexpected loss of GFR in the SRL/MMF group. Differences in renal function between Larson's and other studies may be explained by the different anti-calcineurinic drugs used in the control group because it seems that CsA induces more profound renal hemodynamic changes than TAC, at least at the current target levels for clinical immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations